2003
DOI: 10.1213/01.ane.0000055819.35383.d3
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spondylodiscitis Caused by Propionibacterium acnes After Epidural Obstetric Analgesia

Abstract: We report a case of Propionibacterium acnes spondylodiscitis after the placement of an epidural catheter for obstetric analgesia. This observation should alert the anesthesiologist to the fact that infection, although rare, may occur after uneventful epidural analgesia in the healthy parturient and reinforces the importance of aseptic technique during epidural catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Thirty-three of the 49 women (67%) had a caesarean delivery (either elective or non-elective) and had the epidural catheter retained for postoperative pain relief (median duration 43 h [IQR [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]). In 16 women (33%) the epidural catheter was used only during labour, for a median duration 11 h (IQR 5-22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three of the 49 women (67%) had a caesarean delivery (either elective or non-elective) and had the epidural catheter retained for postoperative pain relief (median duration 43 h [IQR [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]). In 16 women (33%) the epidural catheter was used only during labour, for a median duration 11 h (IQR 5-22).…”
Section: Resultsmentioning
confidence: 99%
“…2,3,9,28 In organizing imaging, it is also important to remember that, as noted in our series, infection may be located in tissues adjacent to the epidural space, including the paravertebral space, paraspinal and adjacent muscles, [29][30][31] and nearby bone or disc. [32][33][34] Treatment of deep tissue infection involves aggressive antibiotic therapy, with or without surgical decompression within 6-12 h. 2 Empirical antibiotic treatment should cover species such as Staphylococcus aureus, Streptococci and Gram-negative bacilli, 3,9 and antibiotic treatment should continue for up to 6 weeks, extending to 8 weeks if osteomyelitis is present. 35 Conservative management without surgical drainage is an option in cases without neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The present review of the literature resulted in 15 reports concerning spondylodiscitis due to P. acnes, which, along with our own cases, are summarized in Table 1. Eleven articles were case reports [14][15][16][17][18][19][20][21][22][23][24] and five were case series [25][26][27][28][29], of which the largest involved four patients [26]. An additional report [29] revealed insufficient information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-established role in the pathogenesis of acnes vulgaris (16,34), it has also been linked to synovitis-acnes-pustulosis-hyperostosis-osteitis syndrome (44,54), sarcoidosis (17), and prostate cancer (14). Recent studies have revealed trauma and surgery as the predisposing factors associated with numerous P. acnes infections, which include brain abscesses (36), osteomyelitis after lumbar puncture (1), discitis after surgery (23), spodylodiscitis following epidural catheterization (22,25), postoperative mediastinitis (19,58), endophthalmitis (7), and endocarditis (21). Furthermore, it is also emerging as an important pathogen in infections related to medical foreign-body implants, such as intraocular lenses (65), ventroperitoneal shunts, orthopedic implants (9,28,51), silicone implants (2), prosthetic heart valves (33,42), and prosthetic joints (38,61).…”
mentioning
confidence: 99%